A citação bibliográfica no contexto da comunicação científica: um estudo exploratório na área da Botânica - Mello, Paula Maria Abrantes Cotta de (1990)
Exploratory analysis about the citation habits of the botanic researchers from "Jardim Botânico do Rio de Janeiro" and "Museu Nacional do Rio de Janeiro" in the scientific community context, trying to identify the reasons with make them choose and quote a document instead of the others, and identify the titles of the most serial publications by the creation and used of questionnaires. The results showed information about the reseachers, its citation and research habits with allowed us to analyse throw means not only formal important aspects of its social organization. The botanic researcher reads day by day in his paper the smplest, the fasted and the most atract literature that he is presented at, publish his papers most of the time in national serials publications printed by the institutions to with they are entailed. The national serial publication of mentions as the most important for thefield and the foreign one as the most relevant for the development of their researches.